(untitled) (Филолошке студије, 2019)
The paper presents four Slovene autobiographical novels: Podobe iz mojega življenja (1964) by Ilka Vašte, Ure mojih dni (1985) by Mira Mihelič, Zaznamovana (1992) and Saga o kovčku (2003) by Nedeljka Pirjevec. Two decades separate respectively the three women writers by their years ob birth and by the publication years of their last works, which should allow for a comparison of the writers’ life stories as well as for a respective autobiographical subject construction. The comparison demonstrates a development of self-consciousness, of acceptance and deconstruction of social roles and of the situation of women in society. The subject has undergone a change from a strong, competitive, rebellious woman, willing to succeed in public sphere, to a softened, yielding, responsive being, eventually ending in an apparent subordination which in fact equals the capability of allowing the other to be and thus overcoming the relation of rivalry between sexes. In this manner essentialist (fatalist) concept of gender is surmounted and a shift into historically variable social constructions of sex roles is achieved. At the same time narrative strategies evolve: a simple dialogue between the narrator and the autobiographical heroine grows into a polyphonic literary structure, the autobiography acquires fictitiousness, and the traditional realistic manner of narration withdraws before minutely elaborated and disseminated modern writing.